Therapeutic effects of hydrogen on chronic graft‐versus‐host disease. Issue 10 (4th April 2017) - Qian, Liren; Liu, Xiaopeng; Shen, Jianliang; Zhao, Defeng; Yin, Wenjie
Abstract: The incidence of chronic graft‐versus‐host disease (cGVHD) is rising recent years, which has been the leading cause of non‐transplantation mortality post allogenetic hematopoietic stem cell transplantation (HSCT). Imbalance of inflammatory cytokines and fibrosis plays critical roles in the pathogenesis of cGVHD. Recent studies showed that molecular hydrogen has anti‐inflammatory, antioxidant, anti‐fibrosis effects. Therefore, we hypothesized that molecular hydrogen may have therapeutic effects on cGVHD. To determine whether hydrogen could protect mice from cGVHD in an MHC‐incompatible murine bone marrow transplantation (BMT) model, survival rates of mice were calculated, and skin lesions were also evaluated after BMT. This article demonstrated that administration of hydrogen‐rich saline increased survival rate of cGVHD mice. Administration of hydrogen‐rich saline after transplantation also reduced skin lesions of cGVHD mice. Previously, we reported the therapeutic effects of hydrogen on acute GVHD. However, there was no report on the therapeutic effects of hydrogen on cGVHD mice. It is suggested that hydrogen has a potential as an effective and safe therapeutic agent on cGVHD. This study will provide new ideas on the treatment of cGVHD and has important theoretical values.